Tilling and biomass production of Chrysopogon zizanioides (L.) submitted to cutting heights and organic fertilization - Rocha, Jaídson Gonçalves da; Coelho, Fábio Cunha; Lelis, Rosana Teixeira; Santos, Gabriela Carvalho de Souza (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Vetiver grass (Chrysopogon zizanioides (L.)) has high agronomic potential and possibilities of use as a source of green manure. Thus, the objective of this work was to evaluate cutting heights of vetiver grass, fertilized in coverage with doses of manure, to use it as a cover plant in organic agriculture. The experiment was carried out under field conditions, in Campos dos Goytacazes, Rio de Janeiro. The experiment consisted of two factors, cutting at four heights (0, 10, 20 and 40 cm) and top dressing at 45 days after cutting with cattle manure (5.4 and 10.8 t ha-1), half of the plants of each height received one of the fertilization doses. The number of tillers at different times, and fresh and dry biomass were evaluated. With the results, it was observed that the height of 40 cm provided the highest tillering, followed by the height of 10 cm, while for fertilization there was no difference; for production of tillers and fresh and dry biomass. The height of 10 cm combined with organic fertilization of 5.4 t ha-1 results in a better agronomic performance of vetiver grass in response to cutting, being recommended for its management as a cover crop.